STRATEGI PEMASARAN USAHA KECIL MENENGAH PADA IBU-IBU AISYIAH MUHAMMADIYAH BALI - Tri Budiyanto (Universitas Ahmad Dahlan, 2020)
Most of the Aisyiah womens in the Muhammadiyah Bali region have side jobs as housewives. Various businesses include Small Medium Enterprises (in Bahasa Indonesia, Usaha Kecil dan Menengah) engaged in grocery stalls, selling cloth, food stalls, furniture businesses, Muslim fashion stores and others. Some of the obstacles faced in developing their businesses include capitalization, management and location determination, as well as the quality of production as well as marketing.The purpose of this service activity is to equip Aisyiah Muhammadiyah Bali women in implementing marketing strategies that are in line with their business and competing in marketing. The benefits of this dedication for Aisyiah's mothers are getting knowledge and understanding related to the marketing field.